2016
DOI: 10.5041/rmmj.10249
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Completion Thyroidectomy for Initially Misdiagnosed Thyroid Carcinoma

Abstract: IntroductionCompletion thyroidectomy is defined as the surgical removal of the remnant thyroid tissue following procedures of less than total or near-total thyroidectomy. Whether thyroid reoperations are associated with an increased complication risk is controversial.ObjectiveA retrospective analysis was done of patients undergoing completion thyroidectomy for cancer of the thyroid who had undergone surgery elsewhere for solitary thyroid nodule. The incidence of surgical complications in these patients after r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…16 The risk of intermittent hypothyroidism is reported as 5.8% to 24.5% in earlier studies accompanied by permanent hypocalcaemia. 2,17 In present research the prevalence of seroma formation was only 3.3%. This low prevalence may have caused none of the cases presenting wound infection formation.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…16 The risk of intermittent hypothyroidism is reported as 5.8% to 24.5% in earlier studies accompanied by permanent hypocalcaemia. 2,17 In present research the prevalence of seroma formation was only 3.3%. This low prevalence may have caused none of the cases presenting wound infection formation.…”
Section: Discussioncontrasting
confidence: 53%
“…1 Around the globe the presentation of these tumours is as single identifiable thyroid node. 2 The diagnosis of thyroid tumour is performed through sonographic imaging as well as cytological assessment of aspirated fine needle samples. Thyroid lobectomy is a standard operating procedure for unilateral thyroid abrasions such as thy-3 and thy-4.…”
Section: Introductionmentioning
confidence: 99%
“…CT has been described as having a higher surgical complication rate than that of total thyroidectomy (TT), which is possibly related to adhesions from the initial procedure 12–14 . There are also studies that support comparable rates of complications between the procedures 10,15,16 .…”
mentioning
confidence: 99%
“…However, the tissue alterations that occur after the initial surgery, such as inflammation, fibrosis, adhesions, and swelling, can complicate the accurate identification of anatomical landmarks during completion thyroidectomy 22 . Consequently, completion thyroidectomy is often perceived as carrying an elevated risk of postoperative complications, including potential injuries to the skin flap or trachea 23 , as well as increased surgical complexity, which can lead to longer operation times compared to the initial surgery 24 . While some studies have suggested that the risks of a two-stage approach of initial thyroid lobectomy followed by completion thyroidectomy may not significantly differ from those of an initial total thyroidectomy 25 , the technical demands of completion thyroidectomy remain significant.…”
Section: Discussionmentioning
confidence: 99%